Evolution of Noman's industries - Ise, Estelle (My University, 1908)
Introduction: Of the billion and a half human beings on the earth one half are females. What this vast multitude are doing in the world’s activities and what their mothers are grandmothers, to the remotest generation backward, have had in originating and developing culture is a question which concerns the whole race.
Citation: Ise, Estelle. Evolution of Noman's industries. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Evolution; Humans; Culture; Noman; Handwritten; Graduating theses; Senior theses; Theses